The Boer War - Barbary, James (Victor Gollancz Ltd : London, 1971)
Discusses the issues and events of the 1899-1902 South African war between the Boers and the British.
'Further reading': p. 203-205.
1
Keywords: South African War, 1899 -- 1902 -- Juvenile literature